Methodological Approaches to Pedagogical Control in Physical Education of Girls Aged 12-14 - Іващенко, О.; Худолій, О. (Physical Education Theory and Methodology, 2016)
The objective is to determine the methodological approaches to pedagogical control in physical education of girls aged 12-14. Materials and methods. The participants of the study were girls aged 12 (n = 31), aged 13 (n = 26), and aged 14 (n = 28). To achieve the tasks set, the study relied on the following methods: analysis of scientific literature, pedagogical testing and methods of mathematical statistics. To evaluate the functional and motor preparedness of the girls aged 12-14, we recorded the results of Stange and Genchi, Serkin and motor tests. Results. The standardized coefficients of the canonical discriminant function allow to determine the relation of the variables contribution to the function result. The first function explains the results variation by 86.8% (p < 0.001), the second — by 13.2% (p < 0.001). The above proves that pedagogical control is possible in physical education based on the classification of the age differences in girls aged 12-14, by the results of their functional, strength and coordination preparedness tested. The structural coefficients of the first canonical discriminant function indicate that a significant difference between the girls aged 12 and the girls aged 13-14 occurs in the level of development of their motor coordination, speed strength and the results of Stange’s test. The structural coefficients of the second canonical discriminant function indicate that a significant difference between the girls aged 13 and 14 occurs in the level of development of the static and relative strength of their arm muscles. Conclusions. The final pedagogical control of motor and functional preparedness of the girls aged 12-14 can rest on the first discriminant function with emphasis on the most informative variables.